A Comparative Analysis of Indigenous Research Guidelines to Inform Genomic Research in Indigenous Communities - Jay Maddock; Nicole K. Taniguchi (International Indigenous Policy Journal, 2012)
BACKGROUND: Genetic research has potential benefits for improving health, such as identifying molecular characteristics of a disease, understanding disease prevalence and treatment, and developing treatments tailored to patients based on individual genetic characteristics of their disease. Indigenous people are often targeted for genetic research because genes are easier to study in communities that practice endogamy. Therefore, populations perceived to be more homogenous, such as Indigenous peoples, are ideal for genetic studies. While Indigenous communities remain the focal point of many genomic studies, some result in harm and unethical practice. Unfortunately, the harms of poorly formulated and unethical research involving Indigenous people have created barriers to participation that prevent critical and lifesaving research. These harms have led a number of Indigenous communities to develop guidelines for engaging with researchers to assist in safely bridging the gap between genetic research and Indigenous peoples.SPECIFIC AIMS: The specific aims of this study were: (1) to conduct an international review and comparison of Indigenous research guidelines that highlight topics regarding genetics and use of biological samples and identify commonalities and differences among ethical principles of concern to Indigenous peoples; and (2) develop policy recommendations for Indigenous populations interested in creating formal policies around the use of genetic information and protection of biological samples using data from specific aim 1.METHODS: A comparative analysis was performed to identify best research practices and recommendations for Indigenous groups from four countries: Canada, New Zealand, Australia, and the United States. The analysis examined commonalities in political relationships, which support self-determination among these Indigenous communities to control their data. Current international Indigenous guidelines were analyzed to review processes of how genetic research is conducted and the use of biological samples is handled with Indigenous peoples.RESULTS: Results suggest the need for genetic and genomic research policies for the world’s Indigenous people. Indigenous groups are most vulnerable to research exploitation and harm; therefore, identifying principles that work for Indigenous people will lead to best practices for all populations.CONCLUSIONS: Development and implementation of best practices informed by research guidelines in Canada, New Zealand, Australia, and the U.S. may be helpful to advise Indigenous leaders, policy makers, and researchers to the proper conduction of genetic research within Indigenous communities. Comparative analyses are a useful tool for identifying areas for further work in developing genetic research policy for Indigenous communities.OUTCOME: The outcomes of this analysis are relevant and useful to Indigenous communities and inform the development of community-based genetic research guidelines. The recommendations can be used in designing appropriate policies for future genomic research with Indigenous peoples.